2020
DOI: 10.1108/emjb-02-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

The role of firm location and agglomeration economies on export propensity: the case of Portuguese SMEs

Abstract: PurposeThe present study seeks to assess whether the firm's location and agglomeration economies affect the firm's export propensity.Design/methodology/approachThis work is based on a sample of 20,234 Portuguese manufacturing small and medium enterprises (SMEs) and resort to the estimation of a probit model.FindingsEmpirical results show that the location and agglomeration economies have an important role in determining the firm's export propensity. In particular, the study concludes that SMEs located in coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For example, Amato et al (2021) found that in Spain, export spillovers have a positive impact on the export propensity of small family-managed firms, particularly in low-tech industries. Forte and Sá (2021) similarly found that for Portuguese firms, export spillovers tend to positively affect the export propensity of micro firms and firms in low-tech industries. Koenig et al (2010) found that for French companies, this factor seems to influence export propensity but not export volume, and it has a stronger influence when analyzing a specific product or destination.…”
Section: Introductionmentioning
confidence: 77%
“…For example, Amato et al (2021) found that in Spain, export spillovers have a positive impact on the export propensity of small family-managed firms, particularly in low-tech industries. Forte and Sá (2021) similarly found that for Portuguese firms, export spillovers tend to positively affect the export propensity of micro firms and firms in low-tech industries. Koenig et al (2010) found that for French companies, this factor seems to influence export propensity but not export volume, and it has a stronger influence when analyzing a specific product or destination.…”
Section: Introductionmentioning
confidence: 77%
“…In such a complex situation, manufacturing SMEs intending to enter international markets find challenges in doing so (Healy et al, 2018;Forte and S a, 2021). Entry mode strategies are associated with issues of mergers, acquisitions, green field investments and so on (Xing et al, 2017;Lin et al, 2019).…”
Section: Internationalization (Int)mentioning
confidence: 99%
“…For the small and medium enterprises (SMEs), things are not easy, as they face several challenges (Ferreira and Franco, 2020;Chandra et al, 2021;Forte and S a, 2021). The present study has attempted to investigate how manufacturing SMEs could successfully internationalize their businesses with the help of product-service innovation (servitization) (Saridakis et al, 2019).…”
mentioning
confidence: 99%
“…Organizations must be able to cope with frequently changing conditions of the markets and thrive by exploiting emerging business opportunities (Lu and Ramamurthy, 2011; Qiao et al , 2021; Forte and Sá, 2021). The convergence of information technology (IT) in business operations is perceived to have provided an opportunity to organizations to reshape their organizational dynamic ability to develop their IEA (Bharadwaj, 2000; Prahalad and Krishnan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%